2021
DOI: 10.1002/cnm.3512
|View full text |Cite
|
Sign up to set email alerts
|

Effects of control temperature, ablation time, and background tissue in radiofrequency ablation of osteoid osteoma: A computer modeling study

Abstract: To study the effects of the control temperature, ablation time, and the background tissue surrounding the tumor on the size of the ablation zone on radiofrequency ablation (RFA) of osteoid osteoma (OO). Finite element models of non‐cooled temperature‐controlled RFA of typical OOs were developed to determine the resulting ablation radius at control temperatures of 70, 80, and 90°C. Three different geometries were used, mimicking common cases of OO. The ablation radius was obtained by using the Arrhenius equatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…There are m samples in the array (m ≥ 2 and odd). N [0] denotes the first sample value, N [1] denotes the second sample value, and so on, N [m-1] denotes the mth and last sample value. The details are as follows.…”
Section: Filtering Algorithm Designmentioning
confidence: 99%
“…There are m samples in the array (m ≥ 2 and odd). N [0] denotes the first sample value, N [1] denotes the second sample value, and so on, N [m-1] denotes the mth and last sample value. The details are as follows.…”
Section: Filtering Algorithm Designmentioning
confidence: 99%
“…The amount of time necessary for ablation can vary based on different factors including the electrodes' diameter, tumor size, and power input. However, literature shows average times between 4 and 6 minutes and some even longer [25], while clinical trials have demonstrated ablation times below 4 minutes. The power values were calculated using the microcoil's resistance (11 Ω) and corresponding current values (50 mA, 100 mA, 200 mA, and 0.25 mA).…”
Section: G Tumor Ablationmentioning
confidence: 99%
“…When the temperature between the radiofrequency electrode and the tumour tissue exceeds 100 °C, the tumour tissue will carbonise, resulting in a sharp increase in the impedance of the tumour tissue, which reduces the radiofrequency current density and limits the final ablation effect [7,8]. In addition, different temperatures can affect the ablation volume, and inappropriate temperatures can cause thermal damage to the normal tissue surrounding the tumour, which can lead to a range of complications [9][10][11][12][13][14]. Therefore, stable and accurate temperature control needs to be achieved to improve the therapeutic effect of RFA.…”
Section: Introductionmentioning
confidence: 99%